Capacity credit of concentrating solar power. Issue 6 (1st November 2013) - Usaola, Julio
Abstract : Concentrating solar power technology (CSP) will probably become increasingly present in power systems and will have to be included in generation adequacy studies. CSP has two special features which makes it different from other technologies: its daily and seasonal cycle and its possibility of storage. This study proposes a sequential Monte Carlo method, which includes series of possible trajectories of CSP production to find the capacity value of this technology. From the generated CSP production trajectories, values of loss of load probability, equivalent load carrying capacity and equivalent conventional power plant are calculated. Different hypotheses are considered, in order to study the effect of location of CSP plants, their storage capacity and demand profile on capacity credit. The study has a two fold objective: it intends to propose a way of including CSP in generation adequacy studies, and gives representative values of the contribution of this technology to overall power system reliability.